Iran Heritage Report - Iran Heritage Foundation (London Iran Heritage Foundation, 2010)
In 2010 a significant array of cultural programs were organized by IHF or with their assistance, the highlights of the book are: 1- Epic of the Persian kings. 2- A series of events and programs centered on the special exhibition of the same title at the Fitzwilliam Museum. 3- Seven conference and symposia covering a range of topic. 4- A series of film screening by establishment and emerging Iranian filmmakers and director. 5- Social function.
English
Keywords: NX700-750 Patronage of the arts; Iran